Android controlled home automation system based on different power optimization modes - Rifat, Md. Salman; Fahad, Maruf Naim (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.